Analisis Faktor-Faktor yang Mempengaruhi Keberlanjutan Bank Sampah di Kota Madiun - Khairunisa, Khairunisa,; Lies Wuryanita Adriyani; Nuzulul Anggi Rizki; Rizki Ainuna Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Madiun City produces approximately 45,000 tons of waste per year, most of which ends up in the Winongo Final Disposal Site (TPA), while a small portion is processed through the community-based waste bank program. Waste banks play a role in reducing waste generation while providing economic value to the community through waste sorting and recycling. This study aims to analyze the effect of community participation on the sustainability of the Mojo Makmur Waste Bank in Mojorejo Subdistrict, Madiun City. The study used a quantitative approach with a sample of 10 waste bank members, data collected through questionnaires and analyzed using multiple linear regression. The results show that community participation through economic benefits, social factors & motivation, and environmental knowledge & education significantly affects the sustainability of the waste bank with an R² of 0.892. In conclusion, active involvement of the community is a key factor in ensuring the sustainability of the Mojo Makmur Waste Bank in Mojorejo Subdistrict, Madiun City.